CONTRASTING FINANCIAL ECOSYSTEMS: A COMPARATIVE ANALYSIS OF LOAN DELINQUENCY'S DIVERGENT PATHWAYS TO HOUSEHOLD WELL-BEING IN BOTSWANA'S RESILIENCE AND ZIMBABWE'S VOLATILITY - Musandipa, Costa; Nkala, Peter; Malunguza, Noble; Mbedzi, Edson (Universitas Nahdlatul Ulama Surabaya, 2025)
Households in many countries continue to experience historically low savings rates, rising loan delinquencies, and inadequate long-term financial planning, underscoring persistent concerns about household financial well-being (HFWB). Despite extensive scholarly attention, the relationship between loan delinquency and HFWB remains inconclusive due to inconsistent empirical findings and the broad conceptual scope of prior studies. Addressing this gap, the present study aims to examine the association between loan delinquency measured through non-performing loans (NPLs) and HFWB measured using human development indices in the contexts of Botswana and Zimbabwe. Employing a quantitative research design, the study applies Generalized Additive Models (GAMs) to capture potential non-linear dynamics between the variables. The results show that although economic growth substantially enhances HFWB, its benefits can be attenuated by rising loan delinquency. There are also counterintuitive findings, particularly the direct effect of NPLs on HFWB in Botswana, indicating the need for further qualitative investigation and refinement of HFWB metrics. These findings highlight the importance of strong institutions, effective regulatory frameworks, and proactive credit risk management in building financial resilience. The study offers policy recommendations for governments, financial institutions, and households to foster sustainable improvements in financial well-being.